Regulatory mechanisms underlying the specification of the pupal-homologous stage in a hemimetabolous insect - Ishimaru, Yoshiyasu (Philos Trans R Soc Lond B Biol Sci, 2019)
Juvenile hormones and the genetic interaction between the transcription factors Krüppel homologue 1 (Kr-h1) and Broad (Br) regulate the transformation of insects from immature to adult forms in both types of metamorphosis (holometaboly with a pupal stage versus hemimetaboly with no pupal stage); however, knowledge about the exact instar in which this occurs is limited. Using the hemimetabolous cricket Gryllus bimaculatus (Gb), we demonstrate that a genetic interaction occurs among Gb′Kr-h1, Gb′Br and the adult-specifier transcription factor Gb′E93 from the sixth to final (eighth) nymphal instar. Gb′Kr-h1 and Gb′Br mRNAs were strongly expressed in the abdominal tissues of sixth instar nymphs, with precocious adult moults being induced by Gb′Kr-h1 or Gb′Br knockdown in the sixth instar. The depletion of Gb′Kr-h1 or Gb′Br upregulates Gb′E93 in the sixth instar. By contrast, Gb′E93 knockdown at the sixth instar prevents nymphs transitioning to adults, instead producing supernumerary nymphs. Gb′E93 also represses Gb′Kr-h1 and Gb′Br expression in the penultimate nymphal instar, demonstrating its important role in adult differentiation. Our results suggest that the regulatory mechanisms underlying the pupal transition in holometabolous insects are evolutionarily conserved in hemimetabolous G. bimaculatus, with the penultimate and final nymphal periods being equivalent to the pupal stage. This article is part of the theme issue ‘The evolution of complete metamorphosis’.